Theory of Resources and Capabilities Applied to Organizations from a Quantum Perspective (Global Journal of Management and Business Research, 2023)
The study determines the elements of the theory of resources and capabilities from the theoretical perspectives of the quantum approach in organizations, metacognition, epistemological and ontological approach to the approach of capabilities in the organization, rethought trialectics to enhance business capabilities. The method of the study was docu-mentary with analysis of organizational research and intertwined with philosophical per-spectives. Among the results of the study is the fact that the resources and capabilities of the organization are linked to the quantum view through the management processes and holistic composition of the individuals working in a company, contrary to the mechanistic position in the quantum practice the resources of the company are maximized using an integrative approach, totalizing and direct and permanent communication of all the com-ponents of the organization, both structural and factual, as well as personal and/or subjec-tive, to create synergies between all parties.
Keywords: resources and capabilities; quantum management; enterprises